PENGEMBANGAN KEPRIBADIAN DAN ETIKA KONSELOR UNTUK MEMPERSIAPKAN MAHASISWA BIMBINGAN DAN KONSELING PROFESIONAL - Ariadi Nugraha; Sri Hartini; Khansa Salsabila (JURNAL KONSELING GUSJIGANG, 2020)
The purpose of this research is to develop teaching materials for the development of ethics and personality of counselors which will be used by universities that have guidance and counseling study programs. In addition, the mastery of ethics and personality by prospective counselors helps to achieve the 4 basic competencies that counselors must have. The purpose of this development is carried out due to the lack of understanding of the counselor's ethics and personality as a potential counselor. This is evidenced by the results of the scores obtained by the 6th semester students of Ahmad Dahlan University in participating in UA, out of 198 students, 91 students got a C grade. during lecture activities. The development of this counselor textbook on personality and ethics is expected to be able to facilitate prospective counselors in forming a personality and ethics that should be owned by a counselor.